Avaliação das amplitudes de movimento do cotovelo, antebraço e punho durante manuseio de carga em um setor industrial - Silva, Luciana Cristina da Cunha Bueno (Universidade Federal de São Carlos, 2009)
Despite the intense mechanization that has taken place over recent years, manual material handling still takes place in most occupational environments. Gripping loads have been related with musculoskeletal disorders, but few studies evaluating upper-limb movements by means of direct measurements in occupational environments are available in the literature. The aim of the present study was to describe the types of grip adopted during handling boxes at different heights on industrial pallets, and to record the wrist, forearm and elbow movements. Electrogoniometry was used to record the movements of seven experienced workers during a real activity in an occupational environment. Most of the workers positioned their hands on the load asymmetrically, and the box handles were not used. Large elbow movements and extreme amplitudes of wrist extension and radial deviation were observed according to the different types of grip. The Kruskal-Wallis and post-hoc Dunn tests indicated significant differences in the range of motion for the different heights of the handling task. In order to decrease the load on the upper limbs during manual material handling activities, new box designs associated with worker training, need to be investigated in future studies.
Keywords: Ergonomia; Saúde e trabalho; Lesões musculoesqueléticas - fatores de risco; Eletrogoniometria; Manuseio de carga; Membros superiores; Saúde ocupacional; Prevenção de lesões musculoesqueléticas; Prevention of musculoskeletal disorders; Occupational health; Ergonomics; Electrogoniometer; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL